Ett återbruk av verket: Sonja Åkessons ”Besök på Sandvikens Jernverk” och den arbetarlitterära traditionen - Forsgren, Peter (Tidskrift för litteraturvetenskap, 2017)
Re-using the work. Sonja Åkesson’s ”A visit at Sandviken’s Ironworks” and the tradition of proletarian realism This article examines Sonja Åkesson’s poem ”Besök på Sandvikens Jernverk” (”A visit at Sandviken’s Ironworks”, 1970), and its relation to the tradition of Swedish proletarian realism. By exploring its relations to Stig Sjödin’s collection of poems Sotfragment (Fragments of soot, 1949), and its configuration of male industrial work, the analysis shows several intertextual relations between Åkesson and Sjödin, especially at the thematic level, as they both connect to a tradition in Swedish literature critical against industrial work and capitalism. At the same time, Åkesson adds a critical gender perspective while problematizing class and the role of the poet in ways different from Sjödin.